2022
DOI: 10.1186/s13024-022-00554-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome deregulation of peripheral monocytes and whole blood in GBA-related Parkinson’s disease

Abstract: Background Genetic mutations in beta-glucocerebrosidase (GBA) represent the major genetic risk factor for Parkinson’s disease (PD). GBA participates in both the endo-lysosomal pathway and the immune response, two important mechanisms involved in the pathogenesis of PD. However, modifiers of GBA penetrance have not yet been fully elucidated. Methods We characterized the transcriptomic profiles of circulating monocytes in a population of patients wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…In agreement, pharmacological Wnt activation was previously shown to rescue defects in dopaminergic neurogenesis [105] and bone matrix deposition [106] in iPSCs derived from patients with GD. Across the identified molecular targets, the top enriched pathway was NOTCH signaling, which has also been previously linked to GBA1 -PD [107].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, pharmacological Wnt activation was previously shown to rescue defects in dopaminergic neurogenesis [105] and bone matrix deposition [106] in iPSCs derived from patients with GD. Across the identified molecular targets, the top enriched pathway was NOTCH signaling, which has also been previously linked to GBA1 -PD [107].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that non-motor symptoms are commonly presented in GBA-NMC. 10,44 GBA pathogenic variants could increase the risk of developing psychotic symptoms and orthostatic hypotension, [45][46][47] since the pathogenic variants contribute to the dysregulation in genes involved in α-synuclein degradation, aging, and amyloid progressing, 48 and the diffusion of Lewy pathology in the brain and peripheral nervous system in the prodromal stage of PD. 49,50 Free water values in the posterior substantia nigra in the GBA-PD group were higher than those in the GBA-NMC.…”
Section: Discussionmentioning
confidence: 99%
“…Use of analyses such as transcriptomics or proteomics can provide insight into the pathogenic mechanisms implicated in PD development in genetically stratified cohorts; however, their applicability in clinical setting is difficult. For instance, transcriptomic profile of monocytes in a cohort of GBA1-PD, sPD, GBA1-NMC, and HC, did not find any specific gene target or biological process related to GBA1 signature, but gene-based outlier analysis in GBA1-NMC showed involvement of mitochondrial function [70]. When the authors performed the same analysis in an independent and larger cohort of whole blood samples, they only marginally replicated the results suggesting cell-specificity [70].…”
Section: Routine Blood Markersmentioning
confidence: 97%
“…For instance, transcriptomic profile of monocytes in a cohort of GBA1-PD, sPD, GBA1-NMC, and HC, did not find any specific gene target or biological process related to GBA1 signature, but gene-based outlier analysis in GBA1-NMC showed involvement of mitochondrial function [70]. When the authors performed the same analysis in an independent and larger cohort of whole blood samples, they only marginally replicated the results suggesting cell-specificity [70]. Another recent study applied unbiased mass-spectrometry phospho-proteomic study in PBMCs to a cohort of LRRK2-G2019S and LRRK2-R1441G carriers (with and without PD).…”
Section: Routine Blood Markersmentioning
confidence: 98%